2017
DOI: 10.1093/geronb/gbx123
|View full text |Cite
|
Sign up to set email alerts
|

Disablement in Context: Neighborhood Characteristics and Their Association With Frailty Onset Among Older Adults

Abstract: Objectives Frailty, an aggregate expression of risk resulting from age- or disease-associated physiologic accumulation, is responsible for large economic and societal costs. Little is known about how the context in which older adult’s live may contribute to differences in frailty. This study clarifies the role of neighborhood structural characteristics and social processes for understanding declines in health status. Method D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…Nonetheless, other factors must come into play in the associations between neighborhood environment and frailty. In Caldwell's study of socio, cultural, and physical aspects of the neighborhood environment and frailty in the United States, perceptions of worsening social cohesion were also associated with an increased incidence of frailty over 5 years (Caldwell et al, 2017). This poorer perception of social cohesion and belonging, allied with worse perceived personal safety, were also found to be determinants of increased frailty levels in Dutch communities (Cramm & Nieboer, 2013); with the hypothesis being that increasing frailty levels impact on levels of outdoor activity and restrict social interactions within the neighborhood, thus contributing negatively to frailty status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, other factors must come into play in the associations between neighborhood environment and frailty. In Caldwell's study of socio, cultural, and physical aspects of the neighborhood environment and frailty in the United States, perceptions of worsening social cohesion were also associated with an increased incidence of frailty over 5 years (Caldwell et al, 2017). This poorer perception of social cohesion and belonging, allied with worse perceived personal safety, were also found to be determinants of increased frailty levels in Dutch communities (Cramm & Nieboer, 2013); with the hypothesis being that increasing frailty levels impact on levels of outdoor activity and restrict social interactions within the neighborhood, thus contributing negatively to frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…Yu’s (Yu et al, 2018) longitudinal study confirmed that objectively assessed proximity to green spaces was associated with improvement of frailty phenotype in Chinese older people (Yu et al, 2018). The perception of poor neighborhood physical disorder, defined as the deterioration of buildings and other visible characteristics, was associated with a higher incidence of phenotypic frailty in a longitudinal study (Caldwell et al, 2017). Another cross-sectional study in China reported that perceptions of the neighborhood environment aesthetic quality and an overall walking environment were associated with less frailty as measured by the FRAIL scale (Ye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Structural differences across neighbourhoods, including social deprivation, can be linked to frailty via the stress pathway or through variations in providing collective resources and opportunities to residents to support their health and wellbeing. [31][32][33][34] Living in socially deprived neighbourhoods may affect health and frailty, by accumulation of stress over time. A recent investigation demonstrated that long-term exposure to deprived neighbourhoods is associated with worse allostatic load: wear and tear on the body likely linked to chronic psychological stress exposure.…”
Section: Discussionmentioning
confidence: 99%
“…social cohesion, social participation) are protective against frailty by creating and maintaining social connections and support networks, and by buffering stress. 31,32,34,35 Availability of recreational and cultural facilities has been associated with slower age-related decline. 36 While perceiving residential areas as unsafe 32 or deteriorating 31 are associated with frailty, likely via higher stress levels, avoidance behaviour and maladaptive coping mechanisms, 31,37 greater access to green space could stimulate engagement in physical and social activities, improving frailty status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation